A meta-analysis of case-reports and case-series of dacrystic epilepsy in children and adolescence - Raybarman, Chandan (International Journal of Contemporary Pediatrics, 2021)
This meta-analysis aimed to advance our knowledge about dacrystic epilepsy in children in the present time. PubMed searches for peer-reviewed case reports and case series were conducted using the keywords “dacrystic epilepsy”, “dacrystic seizures”, “crying epilepsy”, “ictal crying”, “crying seizures”. The databases were developed in accordance with preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. The author collected relevant information to characterise the study population including clinical outcome. Eleven studies out of 353 citations between 1998 and 26 May 2021 met the inclusion criteria, including both single cases and series pertaining to dacrystic epilepsy. Eight case reports and three case series were eligible for this meta-analysis and included twenty one cases. The seizure patterns were dacrystic seizures alone in seven cases (33%), and a combination of dacrystic seizures and gelastic seizures in fourteen cases (67%). Neuroimaging revealed structural abnormality in 95% cases. Hypothalamic hamartoma was found in most of the cases (79%) with combined dacrystic seizures and gelastic seizures, whereas it was found in one case (16%) with dacrystic seizures alone. The other underlying lesions in children with dacrystic seizures alone were subependymal nodules and cortical hamartomas (17%), left mesial temporal sclerosis (33%), and cortical dysplasia (17%). Regarding outcome, antiepileptic drugs alone achieved seizure freedom in four cases (22%) only and others (78%) were difficult to treat cases excluding three cases where treatments were not mentioned. Six cases underwent surgical intervention and two cases received ablative radiotherapy. Lesional dacrystic epilepsy is predominant and pharmaco-resistant in children. However, antiepileptic drugs lead to achieving seizure remission in few cases.